Community Assembly Processes as a Mechanistic Explanation of the Predator-Prey Diversity Relationship in Marine Microbes - Chang, Feng-Hsun; Yang, Jinny Wu; Liu, Ariana Chih-Hsien; Lu, Hsiao-Pei; Gong, Gwo-Ching; Shiah, Fuh-Kwo; Hsieh, Chih-hao (Frontiers in Marine Science, 2021)
Predator and prey α-diversities are often positively associated; yet, understandings of the underlying mechanisms require manipulative experiments and thus remain unclear. We attempt to address this issue by deciphering how α-diversity of predator and prey influences each other’s community assembly processes, which subsequently determine their α-diversity. The occurrence of assembly processes was indicated by the mean pairwise taxonomic index within a community (αMPTI), assuming assembly processes left traceable imprints on species’ phylogeny. Specifically, αMPTI quantifies deviations of observed phylogenetic distances from that of random, so that it can be used to hint at the occurrence of non-random/deterministic assembly processes. Larger αMPTI of a community implies the occurrence of weaker homogenizing deterministic assembly processes, which suggests that this community might be comprised of less similar species and thus has higher α-diversity. We hypothesize that higher predator and prey α-diversity would be positively associated with each other’s αMPTI, which would then be positively associated with their α-diversity. To test the hypothesis, we calculated Shannon diversity and αMPTI for heterotrophic nanoflagellates (HNF; predator) and bacteria (prey) communities in the East China Sea (ECS). The HNF Shannon diversity was found to be positively associated with αMPTI of bacteria, which was then positively associated with bacterial Shannon diversity. In contrast, bacterial Shannon diversity did not correlate with HNF’s αMPTI. We argue that top-down control is one of the explanations to the positive α-diversity association among trophic levels in microbes of the ECS.